2021
DOI: 10.3390/ma15010198
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lightweight Aggregate Impregnation on Selected Concrete Properties

Abstract: The impregnation of lightweight aggregate (LWA) is an alternative method to its pre-moistening, which is used to limit the loss of fresh concrete workability due to the aggregate’s ability to absorb a great amount of mixing water. The aim of this study was to access the effectiveness, by pre-coating LWAs with cement paste, in modifying the properties of concrete composites. Two types of lightweight aggregates (Lytag and Leca) characterized with a relatively open-structure shell were selected. The other changea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 33 publications
(87 reference statements)
0
6
0
Order By: Relevance
“…In designing structures, rheological properties of concrete, such as shrinkage and creep, are also important characteristics. Due to the lower modulus of elasticity of the porous aggregate, lightweight concretes are characterized by increased shrinkage in comparison to NWAC, even by up to 50%, which was confirmed by much research on this phenomenon [7,[16][17][18]. On the other hand, since lightweight concretes have the ability to internal curing owing to water accommodated in LWA, the development of their shrinkage may be slower in time and less dependent on conditions of external curing such as temperature and humidity conditions.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…In designing structures, rheological properties of concrete, such as shrinkage and creep, are also important characteristics. Due to the lower modulus of elasticity of the porous aggregate, lightweight concretes are characterized by increased shrinkage in comparison to NWAC, even by up to 50%, which was confirmed by much research on this phenomenon [7,[16][17][18]. On the other hand, since lightweight concretes have the ability to internal curing owing to water accommodated in LWA, the development of their shrinkage may be slower in time and less dependent on conditions of external curing such as temperature and humidity conditions.…”
Section: Introductionmentioning
confidence: 89%
“…Its particles are characterized by a closed structure of the external shell and a regular, spherical shape. The properties of the aggregate, shown in Table 1, especially crushing resistance and water absorption, indicate that in comparison to other sintered fly ash aggregates [1,2,6,14,18], this LWA may create new opportunities for its application in more advanced fields, e.g., for prestressed structures. Due to its high water absorption the aggregate was initially prewetted to its moisture content corresponding to its water absorption after 24 h (WA 24h ) before application for concrete.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The workability of fresh concrete decreased due to the aggregate absorbing a large amount of mixing water [ 84 ]. The mean water absorption for tested composites was up to 16.7% for reference concretes with non-impregnated LWAs [ 84 ]. Therefore, the workability of LWC also needs to be paid attention to when using impregnation.…”
Section: Performance Of Lightweight Aggregate Self-healing Concretementioning
confidence: 99%
“…The possibility of "self-healing" of cracks was noted by some researchers. For example, in (Domagala & Podolska, 2022) it was shown that water ingress into cracks and other defects in the concrete structure leads to the emergence of the wedging effect. In this case, the strength of concrete is reduced by up to 30 %.…”
Section: Fig 1 Shrinkage Cracks On Concrete Pavementmentioning
confidence: 99%